2021
DOI: 10.1038/s41598-021-81278-5
|View full text |Cite
|
Sign up to set email alerts
|

Mobile device use among emergency department healthcare professionals: prevalence, utilization and attitudes

Abstract: Mobile devices are increasingly permeating healthcare and are being regularly used by healthcare providers. We examined the prevalence and frequency of mobile device use, and perceptions around clinical and personal usage, among healthcare providers (attending physicians, residents, and nurses) in the Emergency Department (ED) of a large academic medical center in Lebanon. Half of the target population (N = 236) completed the cross-sectional electronic questionnaire. Mobile device usage for personal matters wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 23 publications
4
29
1
Order By: Relevance
“…Nevertheless, when these devices are used properly, they have enormous potential to improve medical practice, for instance, by allowing quick access to relevant and evidence-based information, which facilitates decision-making and can help reduce error rates. In a recent survey of professionals in an emergency department, most respondents found mobile devices useful for better coordinating care among providers and beneficial for patient care [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, when these devices are used properly, they have enormous potential to improve medical practice, for instance, by allowing quick access to relevant and evidence-based information, which facilitates decision-making and can help reduce error rates. In a recent survey of professionals in an emergency department, most respondents found mobile devices useful for better coordinating care among providers and beneficial for patient care [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A desirable feature of these apps is that they can be used quickly because of the need to provide a rapid response to the broad spectrum of clinical scenarios occurring in emergency departments. Recent studies on mobile devices and medical apps in emergency rooms [ 9 , 10 ] have shown that the apps most frequently used by emergency health professionals are medical formulary and drug-referencing apps (84.4%), followed by disease diagnosis and management apps (69.5%) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that health care professionals are becoming more and more open to using medical apps to help guide patient care 13–16 . Studies have also shown that residents can improve adherence to guidelines for low‐frequency, high‐acuity emergencies with the help of tech‐enabled solutions 17,18 .…”
Section: Reflective Discussionmentioning
confidence: 99%
“…Its popularity and positive reception among surveyed resident physicians may be in part due to a general acceptance of medical apps by healthcare professionals to help guide patient care. 13 , 14 , 15 , 16 Survey results also show that all users would recommend STAT to less experienced clinicians, since the vast majority felt it was easy to use, helped them better manage emergencies at the point-of-care, and would lead to better patient outcomes.…”
Section: Unresolved Questions and Lessons For The Fieldmentioning
confidence: 99%